The impact of architectural Conservation acts in the sustainability of buildings - The Great Mosque in Dohuk as a case study - Cebar jamel sadiq (Sulaimani Journal for Engineering Sciences, 2014)
The research studies the loss of a lot of the architectural characteristics of the heritage and historical buildings in the Kurdistan region of Iraq. The Great Mosque is one of these buildings, in the old city of Duhok, which is adopted as a model for the study, as it represents the personal and the urban architectural identity of the city. The research emphasis on the importance of the architectural heritage of the city of Dohuk over different periods, particularly the Great Mosque, the landmarks was completely removed due to the negligence of Architectural Conservation, in addition to the renovation and modification that got the mosque through the completely redone during the seventies of the twentieth century. So the research aims to reach the original drawings of the mosque (before the modification and renewal processes), by following the analytical method based on a historical survey of the mosque and the region, containing historical documents, photos and interviews with scientists, historians, residents of the region, and visitors to the mosque before the renovations.